P-015 Influence of Core Infarct Volume and Patient Age on Clinical Outcome in Endovascular Treatment of Large Vessel Occlusion for Acute Stroke. (29th July 2016) - Telischak, N; Faisal, A; Wong, J; Moraff, A; Do, H; Dodd, R; Heit, J; Mlynash, M; Lansberg, M; Albers, G; Marks, M
Abstract : Introduction: Endovascular therapy of acute ischemic stroke is the standard of care, but controversy exists regarding how the size of the pre-treatment infarction and patient age should influence patient selection for endovascular treatment. Magnetic resonance imaging (MRI) with diffusion-weighted imaging (DWI) or computed tomography perfusion (CTP) can estimate the pre-treatment infarct volume (core). Studies have examined the interplay between core and patient age, however to date sufficient data do not exist to guide decision making in octogenarians with stroke. We undertook this study to examine the influence of infarct core and age on clinical outcome. Methods: Patients treated between July 2008 and September 2011 from a previously reported study (DEFUSE2) and all patients treated at our institution between September 2012 and June 2015 who underwent endovascular therapy for anterior circulation stroke using available devices were included. Patient demographic data, stroke risk factors, and treatment details were recorded. Core infarct volumes were determined with either DWI MRI or CBF CTP. The primary outcome was good functional outcome of modified Rankin score 0–2 at 90 days; a secondary measure was TICI 2 B/3 reperfusion. ROC analysis was performed for lesion size and age to determine values above which there was <10% chance of a good clinical outcome. Results: 154 patients (mean 69 years (SD 14), 85 (55%) female) met inclusion criteria and had clinical follow-up. Forty-two (27%) were ≥ 80 years. Median time to imaging was 4.5 hours (IQR 2.9–6.7). 136 patients had pre-treatment MRI and 18 had CTP. TICI 2 B/3 reperfusion was achieved in 91 patients (59%). In univariate analysis, TICI 2 B/3 reperfusion (p < 0.001), core volume (p = 0.02), age (p = 0.001), and baseline NIHSS (p < 0.001) were significant predictors for good outcome. An ROC analysis for core size determined a volume of <45 mL yielded a PPV of at least 10% for good outcome. 44/82 (54%) of patients with <45 ml core and TICI 2 b/3 reperfusion had a good outcome, while 1/9 (11.1%) with >45 ml core and TICI 2 b/3 had a good outcome (p = 0.030). This threshold remained an independent predictor when adjusted for age, NIHSS and TICI 2 B/3 reperfusion (OR = 6.7, 95% CI 1.2–36). In ROC analysis for age, <83 years best differentiated the groups with at least 10% chance of good outcome. An ROC analysis in patients >80 years showed a core of ≤16 mL yielded positive predictive value of 10% or better for a good outcome, but the differences in the rates of good outcome at this threshold were not significant. Conclusion: This study found TICI 2 B/3 reperfusion, core volume, age, and baseline NIHSS were independent predictors for good outcome. ROC analysis demonstrated a core infarct volume of <45 ml had a PPV of at least 10% of yielding a good outcome. For patients >80 years the ROC analysis demonstrated that a core infarct volume of <16 ml had a PPV of 10% or better of yielding a good outcome, suggesting that older patients tolerate a smaller core. However, the current study was underpowered to identify the significance of this threshold. Disclosures: N. Telischak: None. A. Faisal: None. J. Wong: None. A. Moraff: None. H. Do: None. R. Dodd: None. J. Heit: None. M. Mlynash: None. M. Lansberg: None. G. Albers: None. M. Marks: None.